Fail at Scale. - MAURER, BEN (Communications of the ACM, 2015)
The article discusses failure in computer system engineering and examines Internet services company Facebook's approach to failure. Noted causes of failures include individual machine failures, workload changes, and human error. The author goes on to comment on the importance of learning from failure.